Five-year monitoring of the ecological status of the Cymodocea nodosa meadow near the Port of Koper - Orlando-Bonaca, Martina (Annales. Series historia naturalis, 2024)
Seagrass meadows are among the most productive ecosystems in marine environments worldwide and are often considered to symbolise near-pristine conditions on sedimentary bottoms, but their condition is associated to various types of anthropogenic stressors. In the Mediterranean Sea, Cymodocea nodosa is considered an effective indicator of environmental change, due to its universal distribution, its sensitivity to various natural and anthropogenic pressures, and the measurability of the species’ responses to these impacts. The aim of this study is to present the improvement of the ecological status of the C. nodosa meadow near the port of Koper over a period of five years and to compare these results with the reference site in the northern Adriatic Sea.
Keywords: Adriatico settentrionale; Cymodocea nodosa; indice MediSkew; Luka Koper; MediSkew indeks; MediSkew index; northern Adriatic Sea; ocena stanja; Port of Koper; Porto di Capodistria; severni Jadran; status assessment; valutazione dello stato